La fonction mnémonique des cartes à jouer illustrées : Le rôle de la mémoire dans la réception et la diffusion des idées whig à travers le jeu de cartes The Meal Tub Plot (c. 1681) - Sophie Lambea (XVII-XVIII)
The deck of playing cards called The Meal-Tub Plot, illustrated by Francis Barlow (c.1626-1704) and sold in London in 1681, was one of the many anti-Catholic printed documents distributed at the time of the Exclusion Crisis by Whig MPs in order to win public support. The narrative strategies were varied, borrowing from newspapers, fables and even comic strips. However, understanding the meaning of these illustrated playing cards is difficult for today’s reader/observer, as Francis Barlow based the narrative of his illustrations on the memory of events that took place at the end of the seventeenth century and knowledge of the historical and cultural context is necessary to fully understand the satirical scope of the playing cards.Besides, The Meal Tub Plot playing cards were not only intended to entertain, but also to help shape public opinion and the collective memory of the English people, thereby facilitating the accession of William of Orange to the throne in 1689.